METODE SPATIAL MACHINE ANTARA MENCIPTAKAN KONSERVASI KOMODO DAN MENJALIN KEMBALI SAUDARA SEDARAH LEGENDA PUTRI NAJO DI PULAU KOMODO - Joshua Keefe; Agustinus Sutanto (Jurusan Arsitektur dan Perencanaan, 2021)
Starting from a happy life where the human settlement and Komodo dragons live side by side. Generation to another generation, the people of Komodo village have believed in totemism from the legend of Princess Najo who gave birth to two male twins, one in the form of a human and one in the form of a Komodo dragon. At that time, humans shared their prey with the Komodo dragons. Now the Komodo village, whose life is in the tourism sector, will be allocated to another island by the government. When the Komodo people are restless, many dragons swim everywhere. There is a flesh and blood relationship between the Komodo dragon and humans. The residents balked and would rather die than have to move from the village which they called their